An efficient synthesis of sulfonated quinoline diones by copper catalyzed sulfonylation of activated alkenes with sulfonylhydrazides. Issue 14 (28th January 2016) - Wang, Shucheng; Huang, Xuhu; Wang, Qi; Ge, Zemei; Wang, Xin; Li, Runtao
Abstract : A novel and highly efficient cascade synthesis of sulfonated quinoline dione derivatives from N -(2-cyanoaryl) methylacrylamides and sulfonylhydrazides in good yields is described. Abstract : A novel and highly efficient cascade synthesis of sulfonated quinoline dione derivatives from N -(2-cyanoaryl) methylacrylamides and sulfonylhydrazides in good yields is described. The reaction proceeds through radical addition, cyclization, and imine hydrolysis, in which one new C–C bond and one CO bond were formed.